Osteoblastic differentiation of periodontal ligament stem cells on non‐stoichiometric calcium phosphate and titanium surfaces. Issue 6 (27th March 2017) - Winning, Lewis; Robinson, Leanne; Boyd, Adrian R.; El Karim, Ikhlas A.; Lundy, Fionnuala T.; Meenan, Brian J.
Abstract: Bioactive materials offer particular clinical benefits in the field of dental implantology, where differentiation of stem cells towards an osteoblastic lineage is required for osseointegration and appropriate function of implants in vivo . The aim of this study was to evaluate the osteoblastic response of Stro‐1 +ve periodontal ligament stem cells (PDLSCs) to three well‐characterized biomaterial surfaces: an abraded titanium surface (cpTi) control; a polycrystalline titanium surface, with both micro and nanotopography produced by radio frequency magnetron sputtering (TiTi); and the same surface incorporating a sputter deposited calcium phosphate coating (CaP‐TiTi). The CaP‐TiTi surfaces were nonstoichiometric, carbonated, and calcium rich with a Ca/P ratio of 1.74. PDLSCs were grown on each surface in the absence of supplementary osteogneic‐inducing agents. Osteoblastic responses were assessed for up to 21 days in culture by measuring gene expression using real time q‐PCR and via assessment of intracellular alkaline phosphatase (ALP) activity. Gene expression analysis for the CaP‐TiTi surfaces showed a significant late stage up‐regulation of Secreted Phosphoprotein 1. Additionally, there was a significant up‐regulation of the Wnt signaling genes β‐catenin and Wnt Family Member 5 A on days 14 and 21, respectively for the CaP‐TiTi surface. A significant increase in intracellular ALP at day 21 for the CaP‐TiTi surface was also observed. These data suggest that the CaP‐TiTi surfaces provide the bioactive conditions required for direct osteoblastic differentiation of PDLSCs. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1692–1702, 2017.